2010
DOI: 10.1007/s11240-010-9818-1
|View full text |Cite
|
Sign up to set email alerts
|

Axillary shoot proliferation and tuberization of Dioscorea fordii Prain et Burk

Abstract: Dioscorea fordii Prain et Burk., a member of the family Dioscoreaceae, is an important tuberous food in China owing to its edible and medicinal functions. However, the lack of healthy planting material has restricted its production. The present study was an attempt to develop a protocol for in vitro propagation of D. fordii. In an initial two by two (2 2 ) factorial experiment, the effects of culture system and activated charcoal have been observed for axillary shoot proliferation and tuberization of in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
(18 reference statements)
0
13
0
1
Order By: Relevance
“…In the last decade an important number of work has confirmed that temporary immersion stimulates shoot proliferation and growth (see review Etienne and Berthouly, 2002;Quiala et al 2006;Pérez-Alonso et al 2009;Sankar-Thomas and Lieberei, 2011;Yan et al 2011). The high number of shoots obtained in the TIS may be a consequence of the efficient gaseous exchange between the plant tissue and the gas phase inside the vessel.…”
Section: Discussionmentioning
confidence: 98%
“…In the last decade an important number of work has confirmed that temporary immersion stimulates shoot proliferation and growth (see review Etienne and Berthouly, 2002;Quiala et al 2006;Pérez-Alonso et al 2009;Sankar-Thomas and Lieberei, 2011;Yan et al 2011). The high number of shoots obtained in the TIS may be a consequence of the efficient gaseous exchange between the plant tissue and the gas phase inside the vessel.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, for numerous species from the Dioscoreaceae family, BA still remains sufficiently effective for in vitro propagation, e.g., for T. chantrieri (Charoensub et al, 2008), Dioscorea multiflora (de Souza et al, 2011), D. zingiberensis (Chen et al, 2003), and. D. fordii (Yan et al, 2011).…”
Section: Effect Of Cytokinins On Shoot Organogenesismentioning
confidence: 99%
“…A combination of plant growth regulators provided unchanged (high) shoot organogenesis, while the root number per explant increased. The highest number of roots of all tested treatments was produced on MS medium supplemented with zeatin (0.1 mg l -1 ) in combination with NAA (0.05 mg l -1 many species of the Dioscoreaceae family, e.g., Dioscorea zingiberensis (Chen et al, 2003), D. fordii (Yan et al, 2011), andD. multiflora (de Souza et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Micropropagation technologies must be used to cultivate this plant to ensure its continued availability and economic value. Many micropropagation protocols have been developed using axenic nodal segments of shoot, shoot tip, axillary shoot, foliar explants and PLBs (Martin and Joseph 2006;Shiau et al 2005;Malabadi et al 2005;Luo et al 2008;Yan et al 2010), and PLBs as explants have emerged as an effective and rapid technique (Nayak et al 2002;Santos Díaz and Carranza Á lvarez 2009). Exogenous applications of spermidine and putrescine have been used to promote shooting of Dendrobium PLBs (Wang et al 2009).…”
Section: Introductionmentioning
confidence: 99%